Analysis Four Factors of Customer Interest Towards Bai' Bitsaman Ajil (BBA) Financing at KJKS BMT Agam Madani Nagari Pakan Sinayan Banuhampu District - Amuz, Annisa; Fahlefi, Rizal; Effendi, Amri (Jurnal Ekonomi dan Perbankan Syariah, 2023)
In economic activities, the main challenge faced is the problem of business capital. This is often the main reason why someone's business does not experience development or progress. Providing business capital in the form of Bai Bitsaman Ajil (BBA) financing is an effort to support the community in improving their business and welfare. As a result of the research conducted by the author, it can be concluded that the Bai Bitsaman Ajil (BBA) financing procedure that meets the implementation of KJKS BMT Agam Madani Nagari Pakan Sinayan is submitting an application for funding to KJKS BMT Agam Madani Nagari Pakan Sinayan, customer financing application form, completeness of fee administration, after that, KJKS BMT Agam Madani conducted a survey of business premises and residences. After carrying out supervision, a financing board meeting is held, the client will decide whether to obtain financing or not, realize the financing request and finally disburse the financing funds. The factors that influence customer interest in Bai' Bitsaman Ajil (BBA) financing are product factors, service factors, promotional factors and location factors. Of these four factors, it can be seen that many customers are willing to finance Bai Bitsaman Ajil (BBA), which is more dominant due to product factors, because the procedures for financing Bai Bitsaman Ajil (BBA) are easier and faster, do not make things difficult for the community, the requirements are not complicated, financing Bai Bitsaman Ajil (BBA) can be paid in installments and is not too burdensome for customers to pay installments. Bai Bitsaman Ajil (BBA) financing is carried out to avoid usury and the margins are small, there is no guarantee of usage.